ANALYSIS OF THE EFFECT OF FUEL SUBSIDY POLICY ON ECONOMIC GROWTH IN INDONESIA - Amanda, Debby; Fadila, Zuyyina Nur; Leonita, Afriza; Uswatunnabila, Anissa; Nurhaini, Siti; Saputri, Sandra (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
This study aims to determine the effect of fuel subsidy policy on economic growth in Indonesia. Fuel oil (BBM) is one of the energy needed by the community as fuel for vehicles, both private and for public vehicles. In Indonesia, the fuel price increased in September 2022, where one example is the price of pertalite fuel, which was originally IDR 7,650 per liter to IDR 10,000 per liter. One of the factors causing this is the conflict between Russia-Ukraine which affects world oil prices to increase. To overcome this, the government made several policies including providing fuel subsidies to the community to launch their activities to increase economic growth in Indonesia. Keywords: Fuel, Subsidy Policy, Economic Growt